Republic of Latvia : 2010 Article IV Consultation Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Republic of Latvia. (IMF Staff Country Reports; Country Report ;, 2010)
Policy efforts in Latvia have supported stabilization. Immediate risks are much lower, but medium-term challenges remain. The government should focus on durable spending cuts, but revenue measures may also be required. Efforts to strengthen regulation and supervision to improve financial stability, including reducing reliance on wholesale external funding, is commended. With monetary and fiscal policy constrained by the fixed exchange rate and the need to reduce the deficit, growth depends on structural reform. While economic and financial conditions are much improved, risks remain significant.